Fishes (Actinopterygii) of the rapids and associated environments in the lower Vaupés River Basin: an undiscovered Colombian Amazon diversity (2024)
The Vaupés River stands out as one of the few within the Amazon basin due to its numerous rapids. These riverine fast-flowing sections not only provide habitat to highly specialized fishes but also function as natural barriers hindering the movement of fish along its course. During a fish-collecting expedition in the lower Vaupés River basin in Colombia, 95 species were registered belonging to 30 families and seven orders. Despite recent inventories in the region, our comprehensive sampling efforts particularly focused on the rapids and associated rheophilic fauna, allowing us to contribute the first records of four fish species in Colombia (Myloplus lucienae Andrade, Ota, Bastos & Jégu, 2016, Tometes makue Jégu, Santos & Jégu, 2002, also first record of the genus, Leptodoras praelongus (Myers & Weitzman, 1956), and Eigenmannia matintapereira Peixoto, Dutra & Wosiacki, 2015) and six presumably undescribed species (i.e., Jupiaba sp., Moenkhausia sp., Phenacogaster sp., Bunocephalus sp., Hemiancistrus sp., and Archolaemus sp.). In this study, a commented list of the ichthyofauna of these environments is presented, as well as a photographic catalog of fish species integrated into the CaVFish Project – Colombia